Raised Alpha-Fetoprotein Level and its Association with Hepatocellular Carcinoma - Madiha Hashmi; Ghulam Haider; Muhammad Danish; Anusha Hassan; Razia Irshad; Khalil Ahmed (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate raised alpha feto-protein levels for socio-demographic and clinicopathological features in hepatocellular carcinoma.